"case \\_1: \\quad \\lambda=-p^2<0\\\\\nx^2y''+xy'-p^2y=0\\Rightarrow y_1=x^p,y_2=x^{-p}\\Rightarrow \\\\\ny=c_1\\cdot x^p+c_2\\cdot x^{-p} \\quad and \\quad y'(1)=y'(e^{2\\pi})=0\\Rightarrow c_1=c_2=0.\\\\\ncase \\_2: \\quad \\lambda=0\\\\\nx^2y''+xy'=0 \\Rightarrow y=c_1\\cdot ln(x)+c_2 \\quad and \\quad y'(1)=y'(e^{2\\pi})=0\\Rightarrow c_1=0.\\\\\ncase \\_3: \\quad \\lambda=p^2>0\\\\\nx^2y''+xy'+p^2y=0\\Rightarrow y=c_1sin(pln(x))+c_2cos(pln(x))\\quad and \\quad \\\\ y'(1)=y'(e^{2\\pi})=0\\Rightarrow\\\\\ny'=\\frac{p}{x}(c_1cos(pln(x))-c_2sin(pln(x)))\\Rightarrow c_1=0,\\quad p=\\frac{k}{2},\\quad k\\in Z.\\\\\n\\lambda = (\\frac{k}{2})^2,\\quad y=c_2\\cdot cos(\\frac{k}{2}\\cdot ln(x));"
Comments
Leave a comment